Prevalence of third molar impaction cases at Puskesmas Baturiti II, Tabanan City: Prevalensi kasus impaksi gigi molar tiga di Puskesmas Baturiti II Kota Tabanan - Kresnayana, I Gusti Agung Ngurah Anindya; Pratama, I Wayan Agus Wirya (Makassar Dental Journal PDGI Makassar, 2024)
Wisdom tooth impaction cases must be considered to prevent infection. At UPTD Puskesmas Baturiti II Tabanan Bali dental health problems are still high. The purpose of this study was to determine the prevalence of third molar impaction cases at UPTD Puskesmas Baturiti II Tabanan in the period December 2023-February 2024. The study was conducted observationally with a cross-sectional method. The number of patient visits for third molar impaction cases was 13 patients out of a total of 270 patients; male patients were 5 (38.5%) and female patients were 8 (61.5%). It was concluded that the prevalence of third molar impaction cases at UPTD Puskesmas Baturiti II Tabanan in the period December 2023-February 2024 was 5.5%.